The Critical Edition of Greek Texts. Achievements and Prospects (Minerva, 2017)
The paper focuses on considerations about critical editions: what is an editor, in the frame of the theory of communication; reasons why a text is interesting to be edited; causes of the alterations of texts; a short survey of recent editions of Greek texts (some examples and different kinds of editions), and reflections about some methodological problems in the field of textual criticism, finishing with a final appeal directed to the young philologists, encouraging them to work in this field.
Keywords: textual criticism; greek philology; critical editions; methodology